A randomized controlled trial for the effect of Modified Shenling Baizhu Powder on delaying the illness progress of COPD stable phase patients (GOLD 1–2 stages): A study protocol. Issue 43 (23rd October 2020) - Liu, Yufei; Xie, Xiaohong; Wang, Wujun; Zhao, Keni; Xiao, Wei; Xiao, Jing; Chen, Jianqin; Zeng, Jurong; Chen, Keling
Abstract: Introduction: As one of the most prominent public health and medical problems, Chronic Obstructive Pulmonary Disease (COPD) has a serious impact on the quality of life of participants and may even be life-threatening. While modern medicine has worked well to alleviate the symptoms of COPD, the current situation with this chronic disease is not encouraging. Lung-spleen qi deficiency syndrome is one of the common forms of COPD and the traditional Chinese medicine formula Modified Shenling Baizhu Powder is very frequently used in the treatment of this syndrome. However, no direct evidence is available to support the efficacy and safety of Modified Shenling Baizhu Powder for COPD treatment. Methods: The study is a prospective, randomized, placebo-controlled, double-blind trial in which 270 eligible participants will be randomly assigned to either the experimental or control group in a 1:1 ratio. Both groups will receive the standard Western medication. Meanwhile, participants in the experimental group will undergo Modified Shenling Baizhu Powder, while those in the control group will undergo a matched placebo. The course of treatment is 6 months with 12 months of follow-up. Primary outcome is the forced expiratory volume in 1 second (FEV1) after bronchodi-lator use. The secondary outcomes include the declines and the between-group difference in the change from baseline to 18 months in FEV1 before bronchodilator use; the forced vital capacity (FVC), FEV1/FVC, FEV1%pred after bronchodilator use, modified British medical research council, COPD Assessment Test, St George's Respiratory Questionnaire (SGRQ); frequency, interval, duration and severity of COPD exacerbations; time to first COPD exacerbation; administration of rescue medication and a cost-effectiveness analysis; Smoking status. A safety assessment will also be performed during the trial. Discussion: The results of this trial will provide comprehensive evidence of the efficacy of Modified Shenling Baizhu Powder for early-stage COPD and the potential mechanism by which Modified Shenling Baizhu Powder acts, which may provide reference for the treatment plan of COPD participants. Trial registration: ChiCTR2000037873, Registered 2 September 2020